Analisis Keputusan Indonesia terhadap WHO FCTC pada Masa Kepemimpinan Presiden Joko Widodo Tahun 2014-2019 - Aloysius Anandyo Pambudi (Mandala: Jurnal Ilmu Hubungan Internasional, 2021)
This article aims to analyze Indonesia’s decision on World Health Organization Framework Convention on Tobacco Control (WHO FCTC) in the leadership period of President Joko Widodo from 2014-2019. As one out of nine states which have not to sign and ratify WHO FCTC, historically Indonesia is one of the full drafting member states which actively involved in the convention’s making and negotiations since 1996. However, from 2003 until 2019, Indonesia still refuses to sign or ratify WHO FCTC. From past years, studies about Indonesia’s non-compliance decision on WHO FCTC limited by the analysis focused on domestic factors to explain state’s behavior, non-state actors’ interest, or discourse about tobacco control issues. This article provides an analysis of the state’s (Indonesia) behavior from the systemic level by using the theory of international regime’s functions. By using secondary data obtained from official documents of state or international organizations, books, journals, and other online sources linked to Indonesia’s decision on WHO FCTC, this article shows that Indonesia’s non-compliance decision to WHO FCTC in the leadership of President Joko Widodo from 2014-2019, caused by Indonesian government’s negative interpretations to the legal liability, reducing cost, and information facilitation functions of WHO FCTC.